18-Fluorine-Fluorodeoxyglucose Positron Emission Computer Tomography Imaging in Melioidosis: Valuable but Not Essential - Joshua Bramwell; Natalia Kovaleva; Joshua J. Morigi; Bart J. Currie (Tropical Medicine and Infectious Disease)
Melioidosis is an endemic tropical disease caused by Burkholderia pseudomallei. It typically causes pulmonary disease and bacteraemia but can disseminate to cause multi-organ disease. 18-F FDG PET/CT has an evolving role in diagnosing other infectious diseases, especially where the pathogen or extent of infection is challenging to elucidate clinically and with conventional imaging (CT, US and MRI). We present a case series of patients diagnosed with melioidosis who also underwent 18-F FDG PET/CT from December 18th 2018 to September 30th 2022. Indications for imaging were categorised and analysed as to whether 18-F FDG PET/CT changed management over conventional imaging. Twenty-one 18-F FDG PET/CT scans were performed for sixteen patients. Two scans (9.5%) performed for pyrexia of unknown origin changed management in both cases. Twelve scans (57.1%) performed to ascertain the extent of dissemination of melioidosis changed management in only three (25%) cases. Five scans (23.8%) performed to monitor the response to treatment of known foci changed management in all five cases. Five scans (23.8%) performed for suspected or known malignancy changed management in three (60%) cases. 18-F FDG PET/CT is an emerging tool which improves diagnosis and changes the management of melioidosis when applied judiciously and for well-selected indications.